Administrative theory and large organizations of the future: whither bureaucracy - Gazell, James A.; Darrell L., Pugh
Some writers predicted the end of bureaucracies allegedly beacuse such organisations are unable to adapt to rapidly changing environments. They forecast that bureaucracies whould be supplanted gradually but inexorably by a spate of alternatives, non of which would become dominant to the point of assuming the exalted status of a new paradigm. They answered the question whither bureaucracy? -- in the negative. The central theme of this article is that such forecasts are turning out to be wide of the mark. The authors posit that suggested alternatives to bureaucracies are really just modifications to enhance their adaptability to their dynamic environments. Furthermore, the writers contend that during the
Keywords: Organization; Bureaucracy; Administrative Theory; Public Administration